Recent Advances in Proteomics Research - Magdeldin, Sameh (IntechOpen, 2015)
Proteomics refers to the entire complement of proteins, including modification. This promising discipline has enabled us to study proteins from a massive and comprehensive point of view. The book Recent Advances in Proteomics Research describes in five sections some of the applications of proteomics. This fine research has been written by leading experts worldwide. This book is aimed mainly at those interested in proteins and in the field of proteins, particularly biochemists, biologists, pharmacists, advanced graduate students and postgraduate researchers.